Impact of long-term high-fat diet intake gestational protein-restricted offspring on kidney morphology and function - Rizzi, V. H.G. [UNESP]; Sene, L. D.B. [UNESP]; Fernandez, C. D.B. [UNESP]; Gontijo, J. A.R.; Boer, P. A. [UNESP] (Cambridge University Press (CUP), 2017)
Emerging evidence highlights the far-reaching consequences of high-fat diet (HFD) and obesity on kidney morphological and functional disorders. In the present study, we aim to evaluate the effects of early HFD intake on renal function and morphology in maternal protein-restricted offspring (LP). LP and normal protein-intake offspring (NP) were fed HFD (LPH and NPH, respectively) or standard rodent (LPN and NPN) diet from the 8th to 13th week of age. Blood pressure, kidney function, immunohistochemistry and scanning electron microscopy were analyzed. Increased total cholesterol and low-density lipoprotein serum levels were observed in LPH offspring. The adiposity index was reduced in the (LPN) group and, conversely, increased in the NPH and LPH groups. Blood pressure was higher beyond the 10th week of age in the LPH group compared with the other groups. Decreased urinary sodium excretion was observed in LP offspring, whereas the HFD-treated groups presented a decreased urine pH in a time-dependent fashion. The LPN, NPH and LPH groups showed increased expression of type 1 angiotensin II (AngII) receptor (AT1R), TGF-β1, collagen and fibronectin in the kidneys. Moreover, the adult fetal-programmed offspring showed pronounced effacement of the podocyte foot process associated with the rupture of cell membranes and striking urinary protein excretion, exacerbated by HFD treatment. To the best of our knowledge, this is the first study demonstrating that young fetal-programmed offspring submitted to long-term HFD intake have increased susceptibility to renal structural and functional disorders associated with an accentuated stage of fibrosis and tubular dysfunction.
Keywords: fetal programming; high-fat diet; hypertension; kidney fibrosis; renal function